Oblique derivative problem in a plane sector for strong quasi-linear elliptic second-order equation with perturbed p(x)-Laplacian. (June 2022) - Borsuk, Mikhail
Abstract: We study the behavior near the boundary corner point of bounded weak solutions to the oblique derivative problem for singular p ( x ) -Laplacian equation with strong nonlinearities singular absorption term in a bounded plane sector.